Drilling of carbon fibre reinforced laminates : a study - Luís M. P. Durão (2009)
The distinguishing characteristics of carbon fibre reinforced laminates, like low weight, high strength or stiffness, had resulted in an increase of their use during the last decades. Although parts are normally produced to near-net shape, machining operations like drilling are still needed. In result of composites non-homogeneity, this operation can lead to delamination, considered the most serious kind of damage as it can reduce the load carrying capacity of the joint. A proper choice of tool and cutting parameters can reduce delamination substantially. In this work the results obtained with five different tool geometries are compared. Conclusions show that the choice of adequate drill geometry can reduce thrust forces, thus delamination damage.